The Development of Interacty-Assisted Learning Media for Junior High School Students: Statistics Material - Femilia; Abbas, Nurhayati; Kobandaha, Putri Ekawaty (IKIP Siliwangi, 2025)
The advancement of educational technology has driven the need for innovative learning media, particularly in abstract subjects such as mathematics, including statistics. However, teaching at SMP Negeri 1 Tilango is still predominantly lecture-based and relies on static media, which results in low student engagement and understanding. The purpose of this study is to develop interactive learning media based on Interacty for the statistics material taught to eighth-grade students. This study is a type of research and development (R&D) using the Plomp development model, which consists of five phases: initial investigation, design, realization/construction, test-evaluation-revision, and implementation. The subjects of this study were eighth-grade students at SMP Negeri 1 Tilango. Validation was conducted by media and content experts, resulting in feasibility percentages of 83.3% (highly feasible) and 80% (feasible), respectively. The limited product trial also showed very positive responses from both teachers (93.75%) and students (86.59%). These results indicate that the interactive learning media based on Interacty meets the criteria of practicality and feasibility in terms of both content and media. Therefore, the developed media is considered suitable for use in the mathematics learning process, particularly in statistics, as it can increase student engagement and help them understand concepts in a more enjoyable and interactive way.